A lecithin phosphatidylserine and phosphatidic acid complex (PAS) reduces symptoms of the premenstrual syndrome (PMS): Results of a randomized, placebo-controlled, double-blind clinical trial - Schmidt, Katja; Weber, Nicole; Steiner, Meir; Meyer, Nadin; Dubberke, Anne; Rutenberg, David; Hellhammer, Juliane (Clinical nutrition ESPEN, 2018)
Many women experience emotional and physical symptoms around the time of ovulation and more so before menstruation interfering with their daily normal life also known as premenstrual syndrome (PMS). Recent observational data suggest that supplementation with Lipogen's phosphatidylserine (PS) and phosphatidic acid (PA) complex (PAS) alleviates these PMS symptoms. The aim of this study was to confirm these observations on the effects of PAS on PMS symptom severity within a controlled clinical trial setting. Forty women aged 18–45 years with a diagnosis of PMS were assigned to either take PAS (containing 400 mg PS & 400 mg PA per day) or a matching placebo. The study comprised 5 on-site visits including 1 baseline menstrual cycle followed by 3 treatment cycles. Treatment intake was controlled for by using an electronic device, the Medication Event Monitoring System (MEMS®). Primary outcome of the study was the PMS symptoms severity as assessed by using the Daily Record of Severity of Problems (DRSP). Further, SIPS questionnaire (a German version of the Premenstrual Symptoms Screening Tool (PSST)), salivary hormone levels (cortisol awakening response (CAR) and evening cortisol levels) as well as serum levels (cortisol, estradiol, progesterone and corticosteroid binding globulin (CBG)) were assessed. PMS symptoms as assessed by the DRSP Total score showed a significantly better improvement (p = 0.001) over a 3 cycles PAS intake as compared to placebo. In addition, PAS treated women reported a greater improvement in physical (p = 0.002) and depressive symptoms (p = 0.068). They also reported a lower reduction of productivity (p = 0.052) and a stronger decrease in interference with relationships with others (p = 0.099) compared to the placebo group. No other DRSP scale or item showed significant results. Likewise, the reduction in the number of subjects fulfilling PMS or premenstrual dysphoric disorder (PMDD) criteria as classified by the SIPS did not differ between the PAS and the placebo group. For the biomarkers, the salivary cortisol percentage increase of the CAR was significantly less pronounced in the follicular phase of cycle 4 than in the follicular phase of cycle 1 for subjects taking PAS when compared to subjects taking placebo (p = 0.018). Furthermore, the change of serum cortisol levels between visit 1 and visit 5 differed significantly between groups (p = 0.043). While serum cortisol levels of PAS treated females slightly decreased between visit 1 and visit 5, cortisol levels of females treated with placebo increased. For all other biomarkers, no treatment effects were observed over the 4 cycles study period. Overall, this study confirms that a daily intake of PAS, containing 400 mg PS and 400 mg PA, can be considered as safe. Results substantiate the efficacy of PAS in reducing symptoms of PMS. In view of the recent inclusion of severe PMS symptoms (PMDD) in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), the positive results of this clinical study merits consideration of developing the PAS complex as a botanical drug for treatment of PMDD. The study is registered at Deutsches Register Klinischer Studien with the registration number DRKS00009005.